Penguatan Pemahaman Keagamaan tentang Keutamaan Memberikan Pendidikan kepada Anak melalui Kajian Kitab Tanqihul Qaul kepada Masyarakat di Desa Juglangan Panji Situbondo - Azisi, Azisi; Badri, Badri; Mulyono, Mulyono; Hidayatullah, Moh Nur (Universitas Pahlawan Tuanku Tambusai, 2024)
This research explores Community Service (PKM) activities carried out by the Nurul Huda Islamic College in Situbondo under the leadership of Azisi, S.Sy., M.Pd. The purpose of PKM is to enrich knowledge and technology, support general welfare, and advance the education sector in accordance with Law Number 20 of 2003 concerning the National Education System. The focus of the research is on PKM activities which focus on strengthening understanding the virtues of providing education to children through the study of the book Tanqihul Qaul in Juglangan Village. Research method by involving community participation through socialization and counseling. And documentation and evaluation of the level of community understanding and practice of knowledge obtained from book studies. This religious strengthening activity has a positive impact as evidenced by the evaluation results which show that the level of understanding of the people of Juglangan Village towards book study reaches 80%, while 20% requires further understanding. In terms of practicing knowledge, 75% of people can practice knowledge well, and 25% require further evaluation.